The Role of Parental Pressure in Relation to Academic Stress and Adolescent Mental Health in Urban Indonesia - Anbar Salma Mardhiyah; Komang Ariyanto; Neuis Marpuah; M Zainul Hafizi; Anie Rohaeni; Feby Arief Nugroho (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2026)
Introduction: This study analyses the impact of parental pressure on academic stress among adolescents in urban Indonesia, emphasizing adolescent mental health as a critical health promotion issue. With increasing evidence of mental health challenges among school-aged youth worldwide, our objective was to investigate how parental expectations and restrictions contribute to academic stress, addressing a gap in the literature on school-based health promotion in Southeast Asia. Methods: We conducted a quantitative cross-sectional survey in leading public high schools in urban Indonesia during the 2024 academic year. A total of 100 students were enrolled through purposive sampling, and data were collected via validated scales that measured parental pressure and academic stress. Ethical approval was obtained from the institutional ethics committee, and all participants provided informed consent before data collection. Results: The primary outcome of the study was the relationship between parental pressure and academic stress. Regression analysis revealed a significant positive correlation between the two variables (R² = 0.566; p < 0.001), indicating that parental pressure had a strong and significant influence on academic stress among adolescents. Additionally, parental restrictions on nonacademic activities were associated with increased stress levels, highlighting the complex nature of parental influence on adolescent well-being. Conclusion: Our study enhances the understanding of adolescent mental health by identifying parental pressure as a key determinant of academic stress. This research emphasizes the need for school-based health promotion strategies that involve parental engagement to foster supportive learning environments. Future studies should investigate culturally tailored interventions to reduce academic stress and improve adolescent well-being, ultimately advancing knowledge in the field of international health promotion.